ANALYSIS OF THE EFFECTIVENESS OF WATERWHEELS AS WATER PUMP DRIVERS - Agung Pradnyana; I Made Anom Adiaksa; I Made Agus Putrawan; I Wayan Suma Wibawa; Made Ardikosa satrya Wibawa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
A pump is a device used to move liquids from one location to another through a pipeline, typically by increasing fluid pressure using electrical power. This increase in pressure helps overcome various types of flow resistance, such as pressure differences, elevation changes, or frictional losses. Transporting fluids from lowland to highland areas is not a simple task, particularly in remote regions where access to electricity is limited. This research was conducted at Pura Beji, Tanah Lot, Beraban Village, Tabanan Regency—an area that has abundant clean water resources in the lowlands compared to the highlands. The study focuses on the process of transferring clean water using water wheels as mechanical drivers in a system known as PATA Technology (Pompa Air Tenaga Air). Therefore, the objective of this research is to analyze the mechanical power generated by the water wheels and the resulting pumping performance of the water pump. This study investigates the effectiveness of waterwheels as mechanical drivers for water pumps in rural areas with limited electricity access, using the PATA (Pompa Air Tenaga Air) system. According to the research result, it was found that for mass flowrate of water wheel 75.5 kg/s then for the mass flowrate of water pump 14.7 kg/s. The efficiency for the waterwheels against the water pump obtained >40%. The water wheels act as the main drive of the water pump through rotation axle gear mechanism which is transmitted to the housing pump with average power water wheel 650 kg.m/s2